The Age, Smoking Habits and Hypertension Incidence in Manado City Community: A Cross-sectional Study - Ivonny Melinda Sapulete; Margareth Rosalinda Sapulete; Ronald Imanuel Ottay; Oksfriani Jufri Sumampouw; Jeini Ester Nelwan; Martin Simanjuntak; Frelly Valentino Kuhon (JURNAL BIOS LOGOS, 2025)
The prevalence of hypertension in Indonesia continues to increase from year to year, especially in the city of Manado. The Central Statistics Agency of Manado City shows that hypertension is the disease with the highest prevalence in Manado City with a total of 27,604 cases in 2020. Hypertension risk factors are divided into 2 major parts, namely unmodified risk factors and modified risk factors. Non-modifiable risk factors such as age over 65 years, family history, and comorbidities such as diabetes mellitus (DM) or kidney disease. Risk factors that can be changed include an unhealthy diet (excessive salt consumption, a diet high in saturated fats and trans fats, low intake of fruits and vegetables), lack of physical activity, tobacco and alcohol consumption, and being overweight or obese. The purpose of this study is to analyze the correlation between age and smoking habits and the incidence of hypertension in the community in the city of Manado. This study is an observational research with a cross-sectional approach. The data was taken in Manado City. Data collection will be carried out in June 2024. Data collection was carried out through interviews using questionnaires. The data were analyzed using the square khi test. The results showed that the most distributed respondents were aged 50 years and over (63.3%), did not smoke (60.0%) and had hypertension (70.0%). The results of bivariate analysis obtained p values of 0.803 (age correlation with hypertension) and 0.328 (correlation between smoking habits and hypertension). This value suggests that there is no significant correlation between age and smoking habits and the incidence of hypertension. It can be concluded that age and smoking are not correlated to the incidence of hypertension in the people of Manado city.